The Negotiation of First Agreements under the Canada Labour Code - Solomon, Norman (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1985)
The purpose of this study is to analyse bargaining units which achieved first agreements and those that did not achieve first agreements in terms of: data relating to their Canada Labour Relations Board (CLRB) certification experience; data relating to basic bargaining unit characteristics; and in terms of data relating to the negotiation of first agreements.